Compositional variation of chrome spinels in the ore-bearing zones of the Kraka ophiolite and the chromitite origin - Saveliev D.E.; Blinov I.A. (Федеральное государственное бюджетное образовательное учреждение высшего профессионального образования «Пермский государственный национальный исследовательский университет», 2017)
The article considers a chemical variation of accessory and ore-forming chrome spinels from the Kraka ultramafic massif at the different scales, from the deposit to the thin section. A correlation analysis of compositional and structural features of ultramafic rocks and ores was performed. The ultramafic rocks and chromitites in the studied massif show the distinct deformation structures and tectonite olivine fabric. A typical chemical gap (i.e. Cr#=Cr/(Cr+Al)) was observed between peridotite, on the one hand, and dunite and chromitite, on the other hand, on the scale of deposits and ore-bearing zones. The location and size of this gap depend on the type of deposit. The gap becomes wider from the disseminated tabular bodies to the typical podiform ones. It has been found that in the thin initial dunite veinlets in peridotite the chrome spinels chemistry changes gradually and there is no Cr# gap between peridotite and dunite. The dunite venlets show a strong olivine fabric, which is an evidence of their high-temperature plastic flow origin. It has been revealed that new chrome spinel grains previously formed as rods or needles and then coarsened. We explained this observation as the result of impurity segregation, coalescence and spheroidization induced by the plastic deformation of olivine. It is inferred that a solid crystal flow is the main requirement for the dunite and chromitite body formation in the Kraka ophiolite massif. In the solid stream, the mineral phase separation takes place. For example, olivine and orthopyroxene grains of parental peridotite separate from one another, and weaker (more mobile) olivine grains form dunite bodies in which chromitite appears as a result of impurity segregation.
Keywords: CHROME SPINEL; OPHIOLITE; ULTRAMAFIC ROCKS; PLASTIC FLOW; PODIFORM CHROMITITE; ХРОМШПИНЕЛИДЫ; ОФИОЛИТЫ; УЛЬТРАМАФИТЫ; ПЛАСТИЧЕСКОЕ ТЕЧЕНИЕ; ПОДИФОРМНЫЕ ХРОМИТИТЫ; 552.321.6+553.46